Progressive methods of transfer and commercialization of new technologies - V. B. Sarkisov; A. I. Sosin (Вестник Северо-Кавказского федерального университета)
In order to form a comprehensive understanding of the essence and prospects of the development of commercialization system of the results of innovative activity, the article examines both traditional and progressive technologies for promoting products of high-tech industries to the market. Special attention is focused on the introduction of fundamentally new approaches to the organization of mechanisms for the support and transfer of innovations, which are based on the identification of potential opportunities and the balance of interests of participants in the process of commercialization of new technologies. To solve the tasks set, a model of effective management of innovative development is proposed, which is an information and functional system aimed at monitoring and supporting high-risk projects, taking into account rapid decision-making in the field of marketing, which in turn will increase the flexibility and adaptability of innovation-oriented enterprises to changing conditions of the external and internal environment.